Electrical conductivity of viscous liquid foods. (November 2018) - Subbiah, Balaji; Morison, Ken R.
Abstract: The electrical conductivities of foods are used for quality assurance, electrical tomography studies and are required for effective simulation of electrical heating processes such as ohmic and microwave heating. Solutions containing milk solids, whey proteins, sugars and sodium carboxymethyl cellulose (NaCMC), with and without electrolytes were prepared and tested. The electrical conductivity was measured using an RCL meter connected to a parallel plate probe. At low concentrations the conductivity increased with concentration, but in some viscous solutions the reduced ion mobility caused a drop in conductivity. The conductivity of sugar solutions could be related to following the modified Walden equation, but that of NaCMC solutions was not influenced by the bulk viscosity. Instead an ion "diffusion viscosity" was defined and calculated from the conductivity. It was found to correspond to the likely viscosity of the solution at a molecular scale. Highlights: The electrical conductivity of a range of model liquid foods was measured. The electrical conductivity of viscous liquid foods is not directly related to bulk viscosity. "Diffusion viscosity" is defined to describe to movement of conducting ions.